1998
DOI: 10.1007/bf02475310
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity and acidity of Al pillared clays and zeolites in different hydrocarbon reactions

Abstract: Abs~a~In comparison with zenlites, a variety of AI pillared clays did not prove as promising cracking catalysts, possibly because their Br6nsted sites are hidden. In the less demanding double bond shift isomerization, both catalyst types were comparable probably due to the presence of Lewis sites on both catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
1
Order By: Relevance
“…also reported the higher yields of liquid product obtained with an Al-pillared clay compared with that obtained with a highly acidic zeolite [ 54 ]. Other comparative studies between Al-pillared clays and zeolites also showed a lower cracking activity of the pillared clay although both types of catalysts are equally active in more facile secondary reactions as a consequence of weakly acidic Lewis sites obviously present on pillared clays as well as on zeolites [ 55 ]. High acidity can also promote a higher extent of secondary reactions leading to the formation of carbon deposits on the catalyst surface with its consequent deactivation [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…also reported the higher yields of liquid product obtained with an Al-pillared clay compared with that obtained with a highly acidic zeolite [ 54 ]. Other comparative studies between Al-pillared clays and zeolites also showed a lower cracking activity of the pillared clay although both types of catalysts are equally active in more facile secondary reactions as a consequence of weakly acidic Lewis sites obviously present on pillared clays as well as on zeolites [ 55 ]. High acidity can also promote a higher extent of secondary reactions leading to the formation of carbon deposits on the catalyst surface with its consequent deactivation [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…They have aluminosilicate frame work structure with three dimensional channels possessing acid sites having potential applications in industrial organic transformations. [1][2][3][4] Clays are aluminosilicates having two dimensional layered structures with stacked frame work arrangement. In clays, such as montmorillonite, negative charge on the layer arises because of isomorphous replacement of structural Al with divalent Mg and Fe ions.…”
Section: Introductionmentioning
confidence: 99%
“…Cations such as Na, Ca and Mg occupy the clay interlayer and neutralize the negative charge. 1,3,5,6 Montmorillonite upon acid treatment undergoes dealumination and forms H + /Al-exchanged clay, an acid catalyst. There are reports in the literature that treatment of montmorillonite with organic acids generates pores on the surface caused by voids due to controlled dealumination in the octahedral layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Böden sind sie ubiquitär als Montmorillonite weit verbreitet. Aufgrund dieser Merkmale stellt die Gruppe der Smektite bereits seit Beginn der 70er Jahre eine immer wieder im Hinblick auf katalytische Interaktionen untersuchte anorganische Komponente des heterogenen Mediums Boden dar (ADAMS et al 1983, BAL-LANTINE et al 1983, FRIPIAT & CRUZ-CUMPLIDO 1974, KÜRSCHNER et al 1998, MORTLAND 1970, MORTLAND 1980, OCCELLI 1987, PINNAVAIA 1983. Die reaktiven Fähigkeiten dieser Tonmineralgruppe sind das Resultat einer extrem kleinen Kristallgröße, von Variationen in der internen chemischen Zusammensetzung, einer hohen Kationenaustauschkapazität, einer großen chemisch aktiven Oberfläche, von Variationen der austauschbaren Kationen und der Oberflächenladung, sowie von Interaktionen mit anorganischen und organischen Verbindungen.…”
Section: Smektite Als Reaktive Tonmineralgruppeunclassified